Using multi-criteria decision-making for selecting a smart metering infrastructure - Echeverri Martinez, Ricardo Andres; Osorio Gómez, Juan Carlos; Echeverry Ibarra, Diego Fernando; Lozano Moncada, Carlos Arturo (Scientia et Technica, 2018)
In this research a methodology based on multi-criteria decision analysis for the evaluation and selection of infrastructure energy smart metering in the Colombian context is presented. The selection process of these measurement infrastructures covers additional technical and financial criteria, becoming a complex problem. The methodology used in this work is the technique called Analytic Hierarchy Process (AHP) that considers seven assessment criteria (Technology, Finance, Environmental, Regulatory, Political, Infrastructure and SocioCultural). Of these assessment criteria, emerge 25 sub-criteria, which are integrated in a hierarchical structure to evaluate three energy smart metering alternatives. Nine experts were consulted to obtain the results. The results show the versatility of AHP method for making complex decisions with respect to the implementation of energy smart metering infrastructure, and provide a useful guide for assessing Smart Grid projects through multi-criteria analysis